(3GdfgGjI aj ZQjH GdMOjK hGdCKQs - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3CMeO Gddg Ydi fYeg HLejY eMGeOg CeG HYO adG NdGa Hjf Chdi GdCdHGH hGdYbhd Cf Yde GdMOjK hGdBKGQ ef CTQa GdYdhe GdESdGejI s
(3BNQgG (B:s
(3ai cJGH GdfHi Ydjg GdSdGe dCbhGd THQh PcQ (B" (3jjYK (B" (3gi HaJM GdjGA GdChdi hVe GdYjf GdegedI (B: (3UbY ef HdGO Gdjef , LYdg dge hGddg CYde hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJ hJUMjMGJs
(3hYdi GdUaMI GdChdi ELGRI ef ESMGb Hf CMeO Hf jMji Hf RcQjG dLeGd GdOjf eMeO Hf YdhGf Hf eMeO HJGQjN SfI (B729(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs